Chitosan-based magnetic nanoparticles for osteosarcoma theranostic - Soares, Paula Isabel Pereira (2018)
Cancer is a well-known disease with a significant impact in society not only due to its incidence, more evident in more developed countries, but also due to the expenses related to medical treat-ments. Cancer research is considered an increasingly logical science with great potential for the development of new treatment options. Advances in nanomedicine have resulted in rapid devel-opment of nanomaterials with considerable potential in cancer diagnostics and treatment. The combination of diagnosis and treatment in a single nano-platform is named theranostic. In this PhD thesis a theranostic system for osteosarcoma was proposed, composed by a magnetic core, a polymeric coating, and a chemotherapeutic drug. The presence of a specific targeting agent, in this case a monoclonal antibody, provides high specificity to the proposed theranostic system. For the core of the proposed theranostic system, stable aqueous suspensions of superparamagnetic iron oxide nanoparticles with an average diameter of 9 nm were produced. Chitosan-based poly-meric nanoparticles with a hydrodynamic diameter around 150 nm were successfully produced. Incorporation of iron oxide nanoparticles into the polymeric ones increased their hydrodynamic diameter to at least 250 nm. A monoclonal antibody specific for a transmembranar protein (car-bonic anhydrase IX) present in solid tumors was developed by hybridoma technology. Functional hybridomas producing the desired monoclonal antibodies were obtained. The proposed theranostic system functionality was evaluated in separated parts of its components. Uncoated and coated iron oxide nanoparticles with chitosan-based polymers generated heat under the application of an external alternating magnetic field. Uncoated iron oxide nanoparticles sta-bilized with oleic acid were able to enhance contrast in magnetic resonance imaging. Drug deliv-ery studies were conducted in chitosan-based polymeric nanoparticles without and with the in-corporation of iron oxide nanoparticles, demonstrating to be an effective drug delivery platform for doxorubicin. The theranostic system proposed in this PhD thesis is very promising for cancer theranostic, demonstrating to be applicable in solid tumors such as osteosarcoma.